Gaze behavior in social interactions between beach volleyball players—An exploratory approach - Nicklas, Andre; Rückel, Lisa-Marie; Noël, Benjamin; Varga, Matyas; Kleinert, Jens; Boss, Martin; Klatt, Stefanie (Frontiers in Psychology, 2022)
Previous research has indicated that social interactions and gaze behavior analyses in a group setting could be essential tools in accomplishing group objectives. However, only a few studies have examined the impact of social interactions on group dynamics in team sports and their influence on team performance. This study aimed to investigate the effects of game performance pressure on the gaze behavior within social interactions between beach volleyball players during game-like situations. Therefore, 18 expert beach volleyball players conducted a high and a low game performance pressure condition while wearing an eye tracking system. The results indicate that higher game performance pressure leads to more and longer fixation on teammates’ faces. A higher need for communication without misunderstandings could explain this adaptation. The longer and more frequent look at the face could improve the receiving of verbal and non-verbal information of the teammate’s face. Further, players showed inter-individual strategies to cope with high game performance pressure regarding their gaze behavior, for example, increasing the number of fixations and the fixation duration on the teammate’s face. Thereby, this study opens a new avenue for research on social interaction and how it is influenced in/through sport.